Production process of grain refinement of aluminum alloy extruded profile
Patent Information
- Application Number
- CN202611209124.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-16
AI Technical Summary
然而,对于高Zn(8.5%~9.7%)、高Cu(1.7%~2.5%)、高Mg(1.6%~2.6%)的复杂合金体系,现有的晶粒细化工艺往往难以兼顾细晶效果与强化相的协同调控
晶粒组织均匀细化,粗晶环得到有效控制:
Smart Images

Figure CN122913276A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum alloy material processing technology, and in particular to a production process for refining the grain size of aluminum alloy extruded profiles. Background Technology
[0002] Ultra-high strength aluminum alloys, due to their excellent specific strength and good corrosion resistance, have become key materials for main load-bearing structural components in the aerospace field. Among them, aluminum alloy sheets and extruded aluminum alloys, with their excellent combination of high strength and corrosion resistance, are widely used in the manufacture of critical structural components such as wing panels, longitudinal beams, and stringers. With the ever-increasing demands for maneuverability, carrying capacity, and fuel efficiency from next-generation aerospace equipment, developing new ultra-high strength aluminum alloy materials with superior overall performance has become an urgent technical challenge.
[0003] However, in pursuing the ultimate strength, ultra-high-strength aluminum alloys face a series of prominent technical contradictions. First, achieving a coordinated improvement in strength, toughness, and corrosion resistance is difficult. While the addition of high-alloying elements is beneficial for precipitation strengthening, it also exacerbates grain boundary brittleness and localized corrosion sensitivity, making it difficult to achieve all three simultaneously. Second, the contradiction between high strength and quenching sensitivity is particularly prominent. During quenching, alloys with high Zn and high Cu content often exhibit uneven microstructure between the core and surface layers of thick, large-section profiles due to the conflict between the tendency for supersaturated solid solution formation and the quenching cooling rate. Furthermore, the manufacturing process window for these alloys is narrow; even minor fluctuations in thermoplastic deformation, solution treatment, and aging processes can significantly affect the type, size, and distribution of precipitated phases, thus determining the overall performance of the final product.
[0004] In the field of aluminum alloy extrusion profile manufacturing, grain refinement is an effective way to improve the overall performance of materials. Fine grain structure can not only improve strength and plasticity through a grain refinement strengthening mechanism, but also improve the corrosion resistance and fatigue performance of the alloy. Existing methods for refining aluminum alloy grains mainly include: modification treatment by adding trace amounts of transition elements (such as Zr, Cr, Mn, Ti, etc.) to increase nucleation sites or inhibit recrystallization grain growth; promoting the uniform precipitation of nanoscale dispersed phases through optimized homogenization treatment processes, providing pinning effects for grain boundary migration during subsequent hot working; and refining the deformed microstructure by controlling thermo-mechanical coupling parameters such as extrusion ratio, extrusion temperature, and extrusion speed, utilizing dynamic recrystallization behavior. However, for complex alloy systems with high Zn (8.5%~9.7%), high Cu (1.7%~2.5%), and high Mg (1.6%~2.6%), existing grain refinement processes often struggle to achieve a synergistic control of grain refinement and strengthening phases. The increased quenching sensitivity and narrowed hot working window brought about by high alloying often result in problems such as uneven grain size, coarse grain rings, or mismatch between the refining effect and the age strengthening response when traditional refining methods are applied to aluminum alloy extrusions. This makes it difficult to meet the stringent requirements of microstructure uniformity and performance consistency for large cross-section profiles used in aerospace.
[0005] Therefore, a grain refinement production process specifically designed for high-alloy aluminum alloy extruded profiles, through multi-dimensional synergistic control of composition, hot working, and heat treatment, can achieve a uniform refinement of grain structure and an effective combination of precipitated strengthening phases. This is of great significance for solving the problem of synergistic improvement of strength, toughness, and corrosion resistance of ultra-high-strength aluminum alloys and promoting the engineering application of high-performance aluminum alloy extruded materials. Summary of the Invention
[0006] This invention provides a production process for refining the grain size of aluminum alloy extruded profiles. It optimizes the reverse extrusion, two-stage solution treatment, and three-stage aging processes, achieving a synergistic improvement in the strength, toughness, and corrosion resistance of the profiles.
[0007] According to one aspect of this disclosure, a production process for refining the grain size of extruded aluminum alloy profiles is provided, the process comprising: S1, calculate the composition data of the aluminum alloy through the phase diagram, and prepare an ultra-high strength aluminum alloy ingot based on the composition data; S2, homogenizes the aluminum alloy obtained in S1; S3, Profile Extrusion: Large-section industrial "T"-shaped profile: Produced according to the process specifications on a 45 kN forward and reverse double-acting extrusion press, using reverse extrusion process, extrusion temperature of 420-460℃, extrusion ratio of 25.6-26.8, and extrusion speed of 0.2 mm / s; S4, the profile is treated through a two-stage solution treatment process; S5, aging treatment is carried out on the profiles after solution treatment: the three-stage regression aging process is as follows: the first stage aging treatment is 120℃ / 24h, the second stage aging treatment is 175℃ for 150min, and the third stage aging treatment is 120℃ / 24h.
[0008] In one possible implementation, in S1, a Ф210mm ingot with good formability is obtained when the casting temperature is 720℃-730℃, the casting speed is 50mm / min-60mm / min, and the cooling water flow rate is 0.02MPa.
[0009] In one possible implementation, in S1, a semi-continuous casting process is used to produce Φ440 mm round ingots, with a casting temperature of 729℃-733℃, a casting speed of 25mm / min, a water pressure of 0.04MPa, and a water temperature of 15℃.
[0010] In one possible implementation, the chemical composition of S1 is as follows by weight percentage: Si ≤0.12%, Fe ≤0.15%, Cu 1.8-2.2%, Mn ≤0.05%, Mg 1.8-2.2%, Cr ≤0.05%, Zn 9.090%, Ti ≤0.10%, Zr 0.08-0.15%.
[0011] In one possible implementation, in S2, the first homogenization process is performed at 430°C for 12 hours, and the second homogenization process is performed at 470°C for 24 hours.
[0012] In one possible implementation, in S3, when the extrusion temperature is 420°C, the degree of recrystallization of the final profile is the lowest, and the maximum value of the fracture toughness of the profile is consistent.
[0013] In one possible implementation, S4 involves treating the profile using a two-stage solution treatment process, including: First-stage solution treatment: 450℃, 2h; second-stage solution treatment: 470-475℃, 4h.
[0014] Compared with the prior art, the beneficial effects of the present invention are: The grain structure is made more uniform and refined, and the coarse grain rings are effectively controlled. Through the synergistic effect of the reverse extrusion process and the two-stage solution treatment, the present invention significantly inhibits the surface recrystallization behavior of the highly alloyed aluminum alloy extruded profile. Under the preferred condition where the extrusion temperature is controlled at 420℃, combined with the low deformation thermal effect of reverse extrusion, the dynamic recrystallization degree of the profile is effectively reduced, the recrystallization degree of the final profile is minimized, and the fracture toughness reaches the highest value. At the same time, through the stepped design of low-temperature pre-solution treatment and high-temperature final solution treatment, the two-stage solution treatment improves the dissolution degree of the insoluble second phase, reduces the recrystallization fraction of the alloy, and promotes the formation of a large number of ultra-fine subgrains in the deformed structure. The above comprehensive effect makes the grain size of the entire cross-section of the large-section "earth"-shaped profile tend to be uniform, effectively eliminates the surface coarse-grained ring defect common in traditional extrusion processes, and lays a microstructure foundation for the consistency of profile properties.
[0015] Synergistic improvement of strength, toughness and corrosion resistance, with excellent comprehensive properties: Aiming at the complex alloy system of ultra-high strength aluminum alloy with high Zn (9.09%), high Cu (1.8%~2.2%) and high Mg (1.8%~2.2%), the present invention innovatively adopts a three-stage regression and re-aging process (120℃ / 24h + 175℃ / 150min + 120℃ / 24h). The first-stage low-temperature pre-aging promotes the uniform nucleation of GP zones, the second-stage medium-temperature aging induces the transformation of intracrystalline precipitated phases to η' phase and promotes the coarsening and discrete distribution of grain boundary precipitated phases, and the third-stage low-temperature re-aging provides supplementary strengthening. Compared with the traditional T6 peak aging, the three-stage aging process of the present invention significantly reduces the local corrosion sensitivity of grain boundaries by regulating the morphology and distribution of grain boundary precipitated phases on the premise of maintaining a hardness level equivalent to that of the T6 state. Thereby, the synergistic matching of the strength, fracture toughness and corrosion resistance of the profile is realized, which meets the strict requirements of aerospace main load-bearing structural parts for the comprehensive properties of materials.
[0016] The process window is widened, and the property consistency of thick and large cross-section profiles is improved: Through the full-process multi-dimensional collaborative regulation of composition-homogenization-extrusion-solution treatment-aging, the present invention effectively reduces the quenching sensitivity caused by high alloying. The homogenization treatment adopts a two-stage system of 430℃ / 12h + 470℃ / 24h, which promotes the uniform precipitation of nano-scale Al3Zr dispersed phases and provides a stable pinning effect for grain boundary migration in the subsequent hot working process. The reverse extrusion process combined with low-temperature extrusion (420℃-460℃) and low-speed extrusion (0.2mm / s) reduces the deformation heat difference between the core part and the surface layer of the thick and large cross-section profile, and makes the grain structures of the core part and the surface layer tend to be consistent. The two-stage solution treatment (450℃ / 2h + 470-475℃ / 4h) effectively avoids the grain coarsening tendency caused by high-temperature and long-time solution treatment, and ensures the uniformity of the solution treatment degree of the entire cross-section of the profile. The above synergistic effect makes the present invention especially suitable for the industrialized and stable production of aluminum alloy profiles for aerospace with large cross-sections and complex cross-sections. Brief Description of the Drawings
[0017] Figure 1 This diagram illustrates a production process flow chart for refining the grain size of an aluminum alloy extruded profile according to an embodiment of the present disclosure.
[0018] Figure 2 A homogenized alloy sample according to an embodiment of this disclosure was subjected to a hot compression simulation experiment with a strain rate of 0.001 s⁻¹. -1 The stress-strain curve diagram.
[0019] Figure 3 The diagram shows the stress-strain curve of a homogenized alloy sample according to an embodiment of the present disclosure at a strain rate of 0.1 s⁻¹ during a hot compression simulation experiment.
[0020] Figure 4 A homogenized alloy sample according to an embodiment of this disclosure was subjected to a hot compression simulation experiment with a strain rate of 10 s. -1 The stress-strain curve diagram.
[0021] Figure 5 The diagram shows the peak rheological stress of an alloy under different deformation conditions (deformation rates) according to an embodiment of the present disclosure.
[0022] Figure 6 The diagram shows the metallographic and SEM microstructure of an extruded alloy according to an embodiment of the present disclosure after treatment at 440℃-460℃ / 2h + 470℃ / 4h.
[0023] Figure 7 The bar chart shows the recrystallization ratio of an alloy according to an embodiment of the present disclosure after solution treatment under different regimes.
[0024] Figure 8 Metallographic and SEM images of alloys after solution treatment at different second-stage solution treatment times according to an embodiment of this disclosure are shown.
[0025] Figure 9 The diagram shows the DSC peak area and conductivity variation curves of an alloy with different secondary solution times according to an embodiment of this disclosure.
[0026] Figure 10 The diagram shows the intragranular precipitate characteristics of an alloy sample according to an embodiment of the present disclosure after regression treatment at 175°C for different times and then aging. (Intragranular precipitate characteristics of the alloy after aging at 120°C / 24h + 175°C / Xmin + 120°C / 24h).
[0027] Figure 11 The diagram shows the intragranular precipitate characteristics of an alloy sample according to an embodiment of the present disclosure after aging at 175°C for different times. (Grain boundary precipitate characteristics after aging at 120°C / 24h + 175°C / Xmin + 120°C / 24h). Detailed Implementation
[0028] Various exemplary embodiments, features, and aspects of this disclosure will now be described in detail with reference to the accompanying drawings. The same reference numerals in the drawings denote elements that have the same or similar functions. Although various aspects of the embodiments are shown in the drawings, they are not necessarily drawn to scale unless specifically indicated otherwise.
[0029] The term “exemplary” as used herein means “serving as an example, embodiment, or illustration.” Any embodiment illustrated herein as “exemplary” is not necessarily to be construed as superior to or better than other embodiments.
[0030] Furthermore, to better illustrate this disclosure, numerous specific details are set forth in the following detailed description. Those skilled in the art will understand that this disclosure can be practiced without certain specific details. In some instances, methods, means, components, and circuits well known to those skilled in the art have not been described in detail in order to highlight the main points of this disclosure.
[0031] A production process for refining the grain size of extruded aluminum alloy profiles, the process comprising: S1, calculate the composition data of the aluminum alloy through the phase diagram, and prepare an ultra-high strength aluminum alloy ingot based on the composition data; In S1, a Ф210mm ingot with good formability is obtained when the casting temperature is 720℃-730℃, the casting speed is 50mm / min-60mm / min, and the cooling water flow rate is 0.02MPa.
[0032] In S1, a semi-continuous casting process is used to produce Φ440 mm round ingots. The casting temperature is 729℃-733℃, the casting speed is 25mm / min, the water pressure is 0.04MPa, and the water temperature is 15℃.
[0033] In S1, the weight percentages of the chemical composition are as follows: Si ≤0.12%, Fe ≤0.15%, Cu 1.8-2.2%, Mn ≤0.05%, Mg 1.8-2.2%, Cr ≤0.05%, Zn 9.090%, Ti ≤0.10%, Zr 0.08-0.15%.
[0034] S2 is a homogenization treatment of the aluminum alloy obtained in S1; in S2, the first homogenization treatment is carried out at 430℃ for 12 hours, and the second homogenization treatment is carried out at 470℃ for 24 hours.
[0035] Experiments have shown that the most suitable hot working range for ultra-high strength aluminum alloys has the following process parameters: deformation temperature 400℃-430℃, deformation rate 0.01s. -1 -0.1s -1This region is a safe and stable area for high power dissipation values of the alloy. Ultra-high strength aluminum alloys can have good hot working performance and can avoid the generation of hot working defects at the same time.
[0036] S3, Profile Extrusion: Large-section industrial "T"-shaped profile: Produced according to the process specifications on a 45 kN forward and reverse double-acting extrusion press, using reverse extrusion process, extrusion temperature of 420-460℃, extrusion ratio of 25.6-26.8, and extrusion speed of 0.2 mm / s; In S3, the final recrystallization degree of the profile is the lowest when the extrusion temperature is 420℃, and the maximum value of the profile's fracture toughness is consistent.
[0037] S4, the profile is treated by a two-stage solution treatment process; S4, the profile is treated by a two-stage solution treatment process, including: first stage solution treatment at 450℃ for 2 hours, second stage solution treatment at 470-475℃ for 4 hours.
[0038] S5, aging treatment is carried out on the profiles after solution treatment: the three-stage regression aging process is as follows: the first stage aging treatment is 120℃ / 24h, the second stage aging treatment is 175℃ for 150min, and the third stage aging treatment is 120℃ / 24h.
[0039] Hot compression simulation experiments were conducted on homogenized alloy samples to obtain the stress-strain characteristics of ultra-high strength aluminum alloys during hot working (strain rate 0.001 s⁻¹ to 10 s⁻¹, deformation temperature 300℃ to 460℃, true strain 0.8). Figures 2-4 The stress-strain curves of ultra-high strength aluminum alloy under different deformation conditions are shown.
[0040] In the initial strain stage, due to work hardening, the flow stress of ultra-high strength alloys rapidly increases to its peak value (when the strain is approximately 0.05). The entire hot deformation behavior of ultra-high strength aluminum alloys is a typical process of competition between work hardening and dynamic softening. However, at 460℃ / 10s... -1 Under deformation conditions, the true stress decreases with increasing true strain, which may be due to deformation instability in ultra-high strength aluminum alloys under these conditions. In the early stages of hot deformation, dislocations in the matrix rapidly multiply and accumulate with increasing deformation, leading to severe work hardening and a significant increase in the flow stress of the alloy. Subsequently, as the deformation intensifies, the stored deformation energy accumulates continuously, and under thermal activation, the deformed microstructure undergoes dynamic recovery and dynamic recrystallization, resulting in work softening. Figure 3 The alloy is at 380℃ / 0.1 s-1 The rheological stress curve exhibits a wavy characteristic, which is a typical feature of dynamic recrystallization of the alloy during hot deformation.
[0041] Analysis of the variation of the true stress peak under different deformation conditions shows that, for example Figure 5 As shown, the true stress gradually decreases with decreasing deformation rate or increasing deformation temperature. At the same deformation temperature, the dislocation content in the alloy's deformed microstructure accumulates rapidly with increasing strain rate, intensifying the interaction between dislocations, increasing the alloy's deformation resistance, and thus increasing its peak flow stress. Simultaneously, as the alloy's strain rate increases, the deformation time shortens, resulting in insufficient dynamic softening of the deformed microstructure, further increasing the peak flow stress. At the same strain rate, with increasing deformation temperature, the thermal activation energy required for alloy deformation decreases, reducing the resistance to dislocation movement and weakening the work hardening effect. Simultaneously, with increasing deformation temperature, the dislocation rearrangement and slip resistance in the matrix gradually decrease, increasing the dynamic softening effect of the alloy's deformed microstructure and decreasing the peak stress value. When the strain rate is constant, increasing the alloy's deformation temperature significantly reduces the peak stress; when the deformation temperature remains constant, increasing the strain rate also increases the peak stress, indicating that aluminum alloys exhibit a positively correlated strain rate sensitivity.
[0042] Table 1 shows the extrusion parameters used in the software simulation of the extrusion process. Table 1 Extrusion process parameters , After solution treatment of ultra-high strength aluminum alloy extruded profiles, due to the relatively high solution temperature, although the residual phases in the alloy can be fully dissolved back into the matrix, the original extrusion deformation structure will undergo recovery and recrystallization behavior. After solution treatment at 475℃ for 4 hours, the recrystallization fraction of the alloy extruded material is about 3.8%. Excessive recrystallization content in the extruded material will cause the loss of the extrusion effect, leading to a decline in the material's mechanical properties and corrosion resistance. A two-stage solution treatment process was adopted to analyze its impact on the alloy microstructure. In the first stage of the two-stage solution treatment process, a relatively low temperature was used to release the deformation energy stored in the alloy during extrusion through microstructure recovery, reducing the driving force for recrystallization. The second stage used a high temperature to eliminate the residual phases in the alloy. Through the combination of high and low temperatures in the two-stage solution treatment, the solution microstructure of the extruded material was further improved, and the overall performance was enhanced. The experimental setup of the two-stage solution treatment process is shown in Table 2 below.
[0043] Table 2. Parameters of the two-stage solution treatment process , The metallographic and SEM structures of the extruded alloy after treatment at 440℃-460℃ / 2h + 470℃ / 4h are as follows: Figure 6As shown, different first-stage solution temperatures have no significant effect on the residual second phase in the alloy. The soluble second phase in the alloy has been fully dissolved back into the matrix. With the increase of the first-stage solution temperature, there are more recrystallized grains in the metallographic structure. This indicates that using a first-stage low-temperature solution can effectively reduce the content of recrystallized structure in the solution alloy.
[0044] The recrystallization content of the alloy samples after solution treatment at 450℃ / (1-4)h + 475℃ / 2h was statistically analyzed. Figure 7 As shown, the degree of recrystallization in the microstructure of the material after heat treatment using a two-stage solution treatment process is significantly lower than that of the sample treated with a single-stage solution treatment at 475℃ / 2h. This is attributed to the fact that the first-stage low-temperature solution treatment can effectively release the deformation storage energy of the extruded alloy through recovery, reducing the recrystallization driving force of the alloy after subsequent high-temperature solution treatment, thereby reducing the degree of recrystallization of the deformed microstructure of the final alloy.
[0045] The first-stage solution treatment was performed at 450℃ for 2 hours. The effect of the second-stage solution treatment time on the alloy's microstructure was verified. The metallographic and SEM microstructures of the alloy after solution treatment are shown below. Figure 8 As shown, with the extension of the secondary solid solution time, the lath structure of the extruded alloy underwent partial recovery and recrystallization; at the same time, the second phase in the alloy was dissolved more and more fully, and the remaining residual second phase was mainly the refractory Fe-rich Al7Cu2Fe phase, with the residual second phase content decreasing significantly to about 0.6%.
[0046] Figure 9 The figures show the changes in DSC peak area and conductivity of the alloy after different two-stage solution treatment times. As the solution treatment time increases, both values decrease continuously, but the decrease is slower than that of single-stage solution treatment. In addition, the comparison shows that the solution treatment under two-stage solution treatment is close to or better than that under single-stage solution treatment, with conductivity less than 15.0 MS / m and DSC peak area equal to or less than 0.5 J / g. This is mainly because the overall time of the two-stage solution treatment process is longer, and the thermal process is longer than that of single-stage solution treatment.
[0047] In summary, considering the effects of solution treatment on the microstructure of ultra-high strength aluminum alloy extrusions, as well as the energy costs and production efficiency in actual production, and the furnace conditions such as the temperature uniformity of the quenching furnace in actual enterprises, the solution treatment process for ultra-high strength aluminum alloys is selected as follows: first stage 450℃ / 2h + second stage 470℃-475℃ / 4h.
[0048] Three-stage regression and re-aging process: Taking a regression temperature of 175℃ as an example, we will verify the influence of different regression times in the range of 120℃ / 24h+175℃ / Xmin+120℃ / 24h (where X is 90min, 120min, 150min and 210min) on the evolution of intragranular and grain boundary precipitates and grain boundary PFZ in aluminum alloys.
[0049] Figure 10 The characteristics of intragranular precipitates in the alloy samples after regression treatment at 175℃ for different times followed by aging are shown. η′ diffraction spots are present in the diffraction patterns of the alloy, indicating a large number of fine, dispersed η′ phases uniformly distributed in the alloy matrix, which is beneficial for improving alloy hardness. When the regression time is 90 min followed by aging, the alloy hardness value increases to 214 HV compared to the solution state at 175 HV, attributed to the precipitation strengthening effect of the fine, dispersed η′ phases. With increasing regression time, the average size of the intragranular precipitates in the final alloy shows a significant increasing trend. This is because, in addition to the precipitates re-dissolving into the matrix during regression, some precipitates also grow and coarsen during regression, resulting in an increase in precipitate size, although still lower than the precipitate size after two-stage aging.
[0050] Overall, after re-aging at 175℃ for 90-210 minutes, the microhardness and electrical conductivity of the alloy after re-aging showed a significant improvement compared to the hardness and electrical conductivity of the solution-treated alloy. However, the hardness of the alloy after re-aging did not change significantly for different re-aging times, remaining within the range of 205HV-215HV, which is within the normal fluctuation range of Vickers hardness testing. However, the fracture toughness of the alloy showed a more significant change, showing a trend of first increasing and then decreasing with the extension of re-aging time. This may be because the extension of re-aging time caused the grain boundary precipitates to coarsen continuously. However, when the size of the grain boundary precipitates reaches a certain level, it is detrimental to the fracture toughness of the alloy.
[0051] like Figure 11 As shown, the grain boundary precipitate characteristics of the regressed reaging alloy are basically similar to those of the two-stage aging alloy. The size of the grain boundary precipitates in the alloy increases continuously with the extension of the regression time. The distribution changes from a single-stage continuous distribution along the grain boundary at 120℃ / 24h to a chain-like distribution, and the spacing between the precipitates increases continuously. In addition, with the extension of the regression time, the PFZ (precipitated zone) at the grain boundary increases continuously and is significantly wider than that of the single-stage aging alloy sample. For example, when the regression time is 90 min, the PFZ width of the final alloy is about 36 nm. When the regression time is extended to 150 min, the PFZ width increases to 69 nm, an increase of nearly 100%.
[0052] After intermediate regression treatment, the intragranular precipitates in the pre-aged alloy at 120℃ / 24h gradually dissolve back into the matrix, while the grain boundary precipitates grow larger, coarser, and exhibit discontinuous distribution, leading to the formation of PFZs, which enhances the alloy's corrosion resistance. During subsequent 120℃ / 24h re-aging, the solute atoms from the dissolved matrix redefine and uniformly distribute within the grains as strengthening phases, significantly increasing the alloy's strength. The three-stage regression-re-aging alloy exhibits a uniformly dispersed precipitate microstructure, possessing strength similar to the T6 peak alloy. Simultaneously, the grain boundary precipitates are coarse and discontinuously distributed, the PFZ width increases, and the grain boundary corrosion channels are broken, hindering the spread of corrosion and giving it two-stage over-aging corrosion resistance.
[0053] With increasing re-aging temperature or extended re-aging time, the mechanical properties of the alloy change relatively little after re-aging, but the fracture toughness shows a phenomenon of first increasing and then decreasing. The average size of intragranular precipitates in the alloy increases slightly but is less than that of two-stage aging. The main strengthening phases in the alloy are the uniformly distributed GP region and η′. The grain boundary precipitates coarsen, evolving from a continuous distribution in the 120℃ / 24h single-stage aging state to a broken chain distribution, and the grain boundary PFZ widens. The optimal three-stage re-aging process is 120℃ / 24h + 175℃ / 150min + 120℃ / 24h. At this time, the average size of intragranular precipitates is between 5nm and 10nm, and the PFZ width is 69nm. It has the intragranular structure characteristics of near single-stage peak aging and the grain boundary structure characteristics of double-stage over-aging. The alloy strength and corrosion resistance are well matched.
[0054] The various embodiments of this disclosure have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A production process for refining the grain size of extruded aluminum alloy profiles, characterized in that, The process includes: S1, calculating the composition data of the aluminum alloy through phase diagram calculation, and preparing an ultra-high strength aluminum alloy ingot according to the composition data; S2, subjecting the aluminum alloy obtained in S1 to homogenization treatment; S3, profile extrusion: large-section industrial "tu"-shaped profile: organized for production on a 45,000 kN forward-backward double-acting extruder according to the process specification, adopting a backward extrusion process, with an extrusion temperature of 420-460°C, an extrusion ratio of 25.6-26.8, and an extrusion speed of 0.2mm / s; S4, treating the profile through a two-stage solution treatment process; S5, subjecting the profile after the solution treatment process to aging treatment: the three-stage regression and re-aging process is that the first-stage aging treatment is at 120°C for 24h, the second-stage aging treatment is at 175°C for 150min, and the third-stage aging treatment is at 120°C for 24h.
2. The production process for refining the grain size of aluminum alloy extruded profiles according to claim 1, characterized in that, In S1, when the casting temperature is 720°C-730°C, the casting speed is 50mm / min-60mm / min, and the cooling water flow pressure is 0.02MPa, a Φ210mm specification ingot with good formability is obtained.
3. The production process for refining the grain size of aluminum alloy extruded profiles according to claim 1, characterized in that, In S1, the semi-continuous casting process is adopted to produce Φ440 mm specification round ingots, with a casting temperature of 729°C-733°C, a casting speed of 25mm / min, a water pressure of 0.04MPa, and a water temperature of 15°C.
4. The production process for refining the grain size of aluminum alloy extruded profiles according to claim 3, characterized in that, In S1, the weight percentages of the chemical components are as follows: Si ≤0.12%, Fe ≤0.15%, Cu 1.8-2.2%, Mn ≤0.05%, Mg 1.8-2.2%, Cr ≤0.05%, Zn 9.090%, Ti ≤0.10%, Zr 0.08-0.15%.
5. The production process for refining the grain size of aluminum alloy extruded profiles according to claim 3, characterized in that, In S2, the first-stage homogenization treatment is at 430°C for 12h, and the second-stage homogenization treatment is at 470°C for 24h.
6. The production process for refining the grain size of aluminum alloy extruded profiles according to claim 1, characterized in that, In S3, when the extrusion temperature is 420°C, the recrystallization degree of the final profile is the lowest, and the maximum value of the fracture toughness of the profile is consistent.
7. The production process for refining the grain size of aluminum alloy extruded profiles according to claim 1, characterized in that, S4, treating the profile through a two-stage solution treatment process, including: The first-stage solution treatment is at 450°C for 2h, and the second-stage solution treatment is at 470-475°C for 4h.